Literature Review: Ethics and Health Law - Irmanjaya Irmanjaya (Faculty of Law, Universitas Pekalongan, 2022)
Humans as social beings grow and develop through interactions with others, requiring norms and ethics in communal life. Ethics and health law are important foundations in maintaining the well-being of individuals and society. This study used a qualitative method with a literature review to collect and analyze information related to the principles of ethics and health law. Ethics, originating from Latin and Greek words, refer to norms of behavior related to human values and customs. Law regulates human behavior in society with the aim of maintaining order and justice, including in the context of health services. Ethics and health law complement each other, where the law tends to be rigid while ethics provide morally responsive guidance to changes. Conflicts between ethics and health law, such as in cases of abortion, emphasize the need for clear policies and a strong moral understanding from medical professionals. The application of ethics and health law in health services, especially in hospitals, influences patient experiences, reflecting practices that are professional and respect patient privacy.